Constitutive Changes in Circulating Follicular Helper T Cells and Their Subsets in Patients with Graves’ Disease - Yan Liu; Xinwang Yuan; Xiaofang Li; Dawei Cui; Jue Xie (Journal of Immunology Research)
Background. Follicular helper T (Tfh) cells are critical for high-affinity antibody generation and B cell maturation and differentiation, which play important roles in autoimmune diseases. Graves’ disease (GD) is one prototype of common organ-specific autoimmune thyroid diseases (AITD) characterized by autoreactive antibodies, suggesting a possible role for Tfh cells in the pathogenesis of GD. Our objective was to explore the role of circulating Tfh cell subsets and associated plasma cells (PCs) in patients with GD. Methods. Thirty-six patients with GD and 20 healthy controls (HC) were enrolled in this study. The frequencies of circulating Tfh cell subsets and PCs were determined by flow cytometry, and plasma cytokines, including interleukin- (IL-) 21, IL-4, IL-17A, and interferon- (IFN-) γ, were measured using an enzyme-linked immunosorbent assay (ELISA). The mRNA expression of transcription factors (Bcl-6, T-bet, GATA-3, and RORγt) in peripheral blood mononuclear cells (PBMCs) was evaluated by real-time quantitative PCR. Results. Compared with HC, the frequencies of circulating CD4+CXCR5+CD45RA−Tfh (cTfh) cells with ICOS and PD-1 expression, the Tfh2 subset (CXCR3−CCR6−Tfh) cells, and PCs (CD19+CD27highCD38high) were significantly increased in the GD patients, but the frequencies of Tfh1 (CXCR3+CCR6−Tfh) and Tfh17 (CXCR3−CCR6+Tfh) subset cells among CD4+T cells were significantly decreased in GD patients. The plasma concentrations of IL-21, IL-4, and IL-17A were elevated in GD patients. Additionally, a positive correlation was found between the frequency of PD-1+Tfh cells (Tfh2 or PCs) and plasma IL-21 concentration (or serum TPO-Ab levels). The mRNA levels of transcription factors (GATA-3 and RORγt) were significantly increased, but T-bet and Bcl-6 mRNA expression was not obviously varied in PBMCs from GD patients. Interestingly, Tfh cell subsets and PCs from GD patients were partly normalized by treatment. Conclusion. Circulating Tfh cell subsets and PCs might play an important role in the pathogenesis of GD, which are potential clues for GD patients’ interventions.